Down-regulation of the placental BCRP/ABCG2 transporter in response to hypoxia signaling. (March 2017) - Francois, Lissa N.; Gorczyca, Ludwik; Du, Jianyao; Bircsak, Kristin M.; Yen, Elizabeth; Wen, Xia; Tu, Mei-Juan; Yu, Ai-Ming; Illsley, Nicholas P.; Zamudio, Stacy; Aleksunes, Lauren M.
Abstract: Introduction: The BCRP/ ABCG2 efflux transporter protects the developing fetus by limiting the transplacental transfer of drugs and chemicals and prevents the apoptosis of trophoblasts. The purpose of this study was to determine whether hypoxia-related signaling alters placental BCRP expression and function in vitro and in human pregnancies. Methods: Human BeWo choriocarcinoma cells were treated with the hypoxia mimetic, cobalt chloride (CoCl2 ), or 3% oxygen for 24–48 h. Activation of HIF-1α signaling and regulation of BCRP was assessed using qPCR, ELISA, western blotting and a fluorescent substrate transport assay. In addition, healthy term placentas from high altitude pregnancies with chronic hypoxia were assessed for BCRP expression. Results: CoCl2 and 3% oxygen increased HIF-1α protein signaling and decreased the mRNA and protein expression of BCRP by 30–75% in BeWo cells. Reduced BCRP expression corresponded with impaired efflux activity during hypoxia as evidenced by accumulation of the substrate Hoechst 33342. A number of transcription factors known to regulate BCRP, including AHR, NRF2 and PPARγ, were also coordinately down-regulated by 3% oxygen in BeWo cells. Moreover, women who gave birth at a high altitude (3100 m) exhibited signs of chronic placental hypoxia, including enhanced protein expression of the HIF-1α target GLUT1, and had reduced BCRP levels in microvillous membranes compared to women at a moderate altitude (1600 m). Discussion: This study provides novel insight into the regulation of the placental BCRP transporter by hypoxia, which may be important for exposure of the fetus to chemicals during early development and in hypoxia-related pregnancy disorders. Graphical abstract: Highlights: Cobalt chloride and low oxygen activate HIF-1α signaling in BeWo placental cells. BCRP expression and function are reduced by HIF-1α signaling in BeWo placental cells. BCRP protein expression is reduced in placentas from high altitude pregnancies. Down-regulation of BCRP in the placenta may increase fetal exposure to chemicals.